Multi-omic analysis of SDHB-deficient pheochromocytomas and paragangliomas identifies metastasis and treatment-related molecular profiles - Aidan Flynn; Andrew D. Pattison; Shiva Balachander; Emma Boehm; Blake Bowen; Trisha Dwight; Fernando J. Rossello; Oliver Hofmann; Luciano Martelotto; Maia Zethoven; Lawrence S. Kirschner; Tobias Else; et al. (Nature Communications)
Abstract Hereditary SDHB-mutant pheochromocytomas (PC) and paragangliomas (PG) are rare tumours with a high propensity to metastasize although their clinical behaviour is unpredictable. To characterize the genomic landscape of these tumours and identify metastasis biomarkers, we perform multi-omic analysis on 94 tumours from 79 patients using seven molecular methods. Sympathetic (chromaffin cell) and parasympathetic (non-chromaffin cell) PCPG have distinct molecular profiles reflecting their cell-of-origin and biochemical profile. TERT and ATRX-alterations are associated with metastatic PCPG and these tumours have an increased mutation load, and distinct transcriptional and telomeric features. Most PCPG have quiet genomes with some rare co-operative driver events, including EPAS1/HIF-2α mutations. Two mechanisms of acquired resistance to DNA alkylating chemotherapies are identifiable; MGMT overexpression and mismatch repair-deficiency causing hypermutation. Our comprehensive multi-omic analysis of SDHB-mutant PCPG therefore identifies features of metastatic disease and treatment response, expanding our understanding of these rare neuroendocrine tumours.